Immediate and short-term adaptations to maximalist and minimalist running shoes. (4th May 2018) - Agresta, Cristine; Kessler, Sarah; Southern, Emily; Goulet, Grant C; Zernicke, Ronald; Zendler, Jessica Deneweth
Abstract: Biomechanical response to running footwear has been studied with regard to traditional shoes and, more recently, minimalist (MIN) shoes. Maximalist (MAX) shoes have grown in popularity as a highly-cushioned counterpoint to MIN shoes. However, little is known about the influence of MAX shoes on running biomechanics alone or in comparison to a MIN shoe design. Because many features of the MIN and MAX shoe are similar (low heel-to-toe drop, minimal stability) with one distinguishing characteristic (cushioning), the primary purpose was to contrast immediate and short-term adaptations to these extreme footwear types. Thirty runners were randomly assigned either the MIN or MAX shoe and ran for four weeks in their assigned shoe. Spatiotemporal measures, vertical ground reaction forces (GRF), lower leg and foot accelerations, and foot strike angle were assessed in the runners' native shoes and both experimental shoes prior to and following the four-week exposure period. Foot strike angle was significantly more plantarflexed and vertical GRF loading rates were significantly higher in both experimental shoes. Running in MIN shoe resulted in higher shank accelerations and lower heel accelerations. Changes from the native shoe were not uniform between the MIN and MAX shoe. No further adaptation was noted at four weeks for either shoe. However, over half the runners using the MIN shoe became injured. Runners appear to immediately respond to changes in heel-toe drop and level of cushioning when running in an unfamiliar shoe. Initial response does not appear to change over a four-week period of running in the unfamiliar shoe. Choosing a MAX shoe may be less risky than MIN shoes when shifting from traditional running footwear, particularly in the initial month of exposure.